Differential effects of sound interventions tuned to 432 Hz or 443 Hz on cardiovascular parameters in cancer patients: a randomized cross-over trial - Hohneck, Anna; Rodríguez, Ánxelo Maia; Weingärtner, Simone; Merx, Kirsten; Sarodnick, Felicitas; von Gagern, Fritjof; Mavratzas, Athanasios; Burkholder, Iris; Schumacher, Gerhard; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter (BMC complementary medicine and therapies, 2025)
This study investigated whether a sound intervention tuned to 432 Hz (Hz) yields differential effects on cardiovascular parameters and psychological outcomes compared to 443 Hz, which is the concert pitch in German professional orchestras. Using a randomized cross-over design, patients with cancer were recruited to receive both a 15-minute sound intervention with a body monochord tuned to 432-443 Hz. Before (pre) and after (post) intervention, cardiovascular parameters were measured using the VascAssist2.0. In addition, visual analogue scales (VAS) for emotional well-being, anxiety, stress, pain and sadness were also assessed pre and post intervention. 43 patients (8 male, 35 female) with a median age of 61 years (range 35-86) were included. Both interventions led to a significant reduction in heart rate with a more pronounced effect for 432 Hz (median reduction − 3 bpm (432 Hz) vs. median reduction − 1 bpm (443 Hz), p = 0.04). While heart rate variability was increased exclusively by 432 Hz (median increase + 3 ms, p = 0.01), both vascular resistance (median reduction − 5%, p = 0.008) and stiffness (median reduction %, p = 0.04) were significantly reduced by 432 Hz, which was not observed at 443 Hz. Nevertheless, these effects were not significantly different compared to 443 Hz. On the other hand, 432 Hz led to a reduced pulse wave velocity (median reduction − 0.5 m/s, p < 0.001), which was also significantly different compared to 443 Hz (p < 0.001). Improvement in VAS was observed for both groups, with significant increases in emotional well-being and reduction in fatigue, anxiety and stress for both intervention timepoints, although the majority showed no increased VAS scores even before the intervention (median values 0 for anxiety and stress). Sound interventions tuned to 432-443 Hz exert both positive effects in cancer patients. While psychological outcomes are improved by both interventions, 432 Hz leads to a more pronounced but not significantly different effect to 443 Hz on objective cardiovascular parameters, which reflect deeper relaxation.